Penerapan Metode SMARTER pada Sistem Pendukung Keputusan Pemilihan Lahan Kayu Putih - Ratih Hafsarah Maharrani; Prih Diantono Abda’u; Hety Dwi Hastuti (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
The productivity of eucalyptus in Indonesia is included in the low productivity group, the lack of raw materials resulting in a deficit in eucalyptus production is the cause of this. Meanwhile market demand is increasing. The large area of land in the Cilacap Regency area is not matched by its utilization, this is due to a lack of knowledge about potential land uses. There are 5 criteria for land, namely land "S1 (Highly Suitable), S2 (Quite Suitable), S3 (marginally suitable), N1 (currently not suitable) and N (not suitable forever). “Decision support methods can be used in determining land suitability, one of which is the SMARTER method. The method was chosen because determining the suitability of eucalyptus land was processed by "rank order centroid (ROC) weighting" where the existing criteria have weight based on the priority level adjusted to the ranking process. Of the 84 processed data, it was found that around 98% or 83 of the data stated that the Cilacap district was included in the S2 suitability range (Quite Appropriate). In addition, based on the results of the accuracy testing carried out, the percentage of accuracy was 80.95%. Seeing the high percentage, the decision support system using the SMARTER method is appropriate to be used to determine the suitability of eucalyptus land. “